1998
DOI: 10.1016/s0378-1097(97)00536-3
|View full text |Cite
|
Sign up to set email alerts
|

NAD-specific glutamate dehydrogenase from Thermus thermophilus HB8: purification and enzymatic properties

Abstract: An NAD-specific glutamate dehydrogenase from Thermus thermophilus HB8 was purified 350-fold by a several-step procedure involving Blue-Sepharose chromatography. The native protein had a molecular mass of approximately 289 kDa, and consisted of six subunits with a molecular mass of 48 kDa each. The optimum pH for the deaminating reaction was 8.0. The optimum temperature was around 85^90³C. NAD-glutamate dehydrogenase showed a high coenzyme specificity, catalysed preferentially glutamate catabolism and presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Ruiz and colleagues have reported that native GDH partially purified from T. thermophilus HB8 is only active in oxidative deamination, and not in reductive amination (Ruiz et al, 1998(Ruiz et al, , 2003. Their results and ours are consistent in that GDH exhibits higher oxidative deamination activity than reductive amination activity.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Ruiz and colleagues have reported that native GDH partially purified from T. thermophilus HB8 is only active in oxidative deamination, and not in reductive amination (Ruiz et al, 1998(Ruiz et al, , 2003. Their results and ours are consistent in that GDH exhibits higher oxidative deamination activity than reductive amination activity.…”
Section: Discussionsupporting
confidence: 79%
“…Native GDH from T. thermophilus HB8 was partially purified and characterized by Ruiz et al (1998Ruiz et al ( , 2003. The purified GDH preparation contained two major bands that showed similar mobility on SDS-PAGE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAD ϩ -dependent GDHs are either tetrameric or hexameric and are mainly involved in glutamate catabolism, while NADP ϩ -dependent GDHs are hexameric and are mainly involved in ammonia assimilation and hence in glutamate synthesis. Catabolic NAD ϩ -dependent GDHs have been found in several microorganisms, including Saccharomyces cerevisiae (34), Candida utilis (9), Neurospora crassa (2,8), Streptomyces fradiae (17), Peptostreptococcus asaccharolyticus (28), Halobacterium halobium (3), Thermus thermophilus (23), Clostridium symbiosum (32), and Clostridium difficile (16), but only a few of these enzymes have been genetically and biochemically characterized (the C. symbiosum, C. difficile, and P. asaccharolyticus enzymes). Of the known gdh genes, the gdh gene of P. asaccharolyticus seems to be suitable for expression in L. lactis, since it is a gene from a gram-positive coccus that is phylogenetically closely related to L. lactis.…”
mentioning
confidence: 99%
“…T. thermophilus possesses two putative gdh genes (gdhA and gdhB) in its genome, both of which encode GDH sharing approximately 46% identity in amino acid sequence. Although GDH has been purified from T. thermophilus HB8 and characterized, 10) it was not clear which isozyme was purified and characterized. Boliver and colleagues reported that recombinant GDH from T. thermophilus HB27, named GdhB in our present study, has GDH activity, 11) however, the function of GdhA remains to be elucidated.…”
mentioning
confidence: 99%